2016
DOI: 10.1016/s2214-109x(16)30215-7
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of 4% chlorhexidine umbilical cord care on neonatal mortality in Southern Province, Zambia (ZamCAT): a cluster-randomised controlled trial

Abstract: Bill & Melinda Gates Foundation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 17 publications
1
64
0
Order By: Relevance
“…However, ensuring adequate health workforce has remained a major challenge for health systems of many developing countries such as Kenya [3] and is likely to continue if the use of CHX for cord care is scaled up. In addition, in light of available evidence from randomized controlled trials showing no difference in neonatal mortality between CHX use and dry cord care among facility-based births in some settings [17, 28, 29], the findings of this paper suggest that scaling up the use of CHX should take into account the community context. In particular, the findings indicate that scaling up the use of CHX would be beneficial in settings where application of harmful traditional substances still exist and where mothers are likely to resort to such practices in the absence of acceptable alternatives due to cultural beliefs about birth and newborn care.…”
Section: Discussionmentioning
confidence: 87%
“…However, ensuring adequate health workforce has remained a major challenge for health systems of many developing countries such as Kenya [3] and is likely to continue if the use of CHX for cord care is scaled up. In addition, in light of available evidence from randomized controlled trials showing no difference in neonatal mortality between CHX use and dry cord care among facility-based births in some settings [17, 28, 29], the findings of this paper suggest that scaling up the use of CHX should take into account the community context. In particular, the findings indicate that scaling up the use of CHX would be beneficial in settings where application of harmful traditional substances still exist and where mothers are likely to resort to such practices in the absence of acceptable alternatives due to cultural beliefs about birth and newborn care.…”
Section: Discussionmentioning
confidence: 87%
“…But results of the effect of 4% CHX applied to the umbilical cord stump on neonatal mortality in the three Asian trials are incongruent with findings in the two African trials. While all studies report an effect of 4% CHX on omphalitis, the African trials [9, 10] did not find an effect on neonatal mortality, unlike the Asian trials [68]. Moreover, none of these studies, particularly the African trials report on the potential effect of CHX on severe illness.…”
Section: Discussionmentioning
confidence: 99%
“…There is a sufficient state of equipoise in Sub-Saharan Africa to justify this study because this intervention has never been tested, and only one study in Asia shows the effect of a single CHX application. Furthermore, two African trials [9, 10] that did not report on severe illness, found no effect of CHX on neonatal mortality, unlike the three Asian trials [68]. …”
Section: Ethics and Disseminationmentioning
confidence: 99%
“…These updated guidelines focused on home births because the South Asian trials that formed the basis of new recommendations were dominated by home births (>90%)[2-4] and the neonatal mortality rate (NMR) in those trials exceeded 30/1000. Two recent studies [5,6] in substantially lower risk settings in Tanzania and Zambia (NMR <11/1000 and <15/1000, respectively) provided no evidence that the intervention would improve survival in settings where mortality was already low. In high-mortality settings, however, policymakers need further guidance on whether or not to extend their emerging chlorhexidine cleansing programs to facility births.…”
Section: Introductionmentioning
confidence: 99%